Pembentukan Paguyuban Pedagang Mie Lethek Kalurahan Caturharjo Bantul Menuju Kampung Wisata Kuliner - Chairunisa Athia Husna; Badriatu Sifri; Zahra Rufaida; Agha Krisannanda Firdaus; Exan Nudin; Andika Rizki Maulana; Devi Nafrilla; Rahma Widya Trisnawati; Nesya Putri Maghfirah; Dini Yuniarti (I-Com: Indonesian Community Journal, 2024)
ABSTRACT According to Indonesia's Intangible Cultural Heritage, Lethek noodles are a typical culinary specialty from Bantul and have the potential of a typical culinary specialty that is inherent in the identity of Caturharjo Village, Bantul. However, these potential losses have not yet had an optimal impact, both on the income of the business actors themselves and the wider sub-district economy. The results of the situation analysis show that one aspect that is a problem is institutional. Partner problems related to institutions are still running independently. There is no lethek noodle business group yet, so development is not yet optimal. For this reason, the Ormawa PPK Team from the Muhammadiyah Student Association, Faculty of Economics and Business, Ahmad Dahlan University provided a solution to this problem by conducting educational outreach on the benefits of community associations and initiating the formation of associations. The method used is community education in the form of socialization lectures and the formation of community associations. Activities will be held on June 30 2024 and July 12 2024. Service participants are lethek noodle business actors and other business actors in Caturharjo District. Apart from that, he was accompanied by the village head, village officials and the heads of the Caturharjo sub-district. Based on responses from partners, it can be concluded that there has been an increase in knowledge, understanding and awareness of the benefits and importance of community associations. One of the indicators is shown by the formation of a Mie Lethek Traders Association with the name "Catur Wastro Boga" Association which has been given a Decree from the Caturharjo District.